DESIGN TO BUILD A TUBER SKIN CLEANING TOOL BY USING DRUM PLAYER CILEMBU VILLAGE JATINANGOR DISTRICT SUMEDANG REGENCY - Bambang Eko Saputro; Muhammad Hernandi (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
As for the design of the tuber washing machine, where the drum is coated with rubber and the drive shaft is coated with nylon thread, there are several important things to consider in this design, including: designing the driving motor power, planning the main components and supporting components: electric motor , reducers, shafts, pulleys, belts, bearings, rubber, cleaning brushes, rotating drums, inlet and outlet funnels, opening and closing handles, engine frames, and machine working drawings. The results of the design are: The tuber playing drum is planned with a diameter of 60 (cm) and a length of 70 (cm), the motor power is used 1.0 (Hp), with a voltage of 220 volts and a frequency of 50 Hz with one phase, and uses a speed reducer with type 50 and a play ratio of 1:50. S35 CD shaft material with tensile stress 53 (kg/mm2), torque 778,504 (kg.mm), shaft diameter 20 (mm) and length 1000 (mm), drive shaft supporting bearing with No.6004VV diameter 20 (mm) , using 2 pulleys with a size of 57 (inches), cleaning rubber mounted on the sides of the drum 160 pieces, cleaning brushes made of nylon thread mounted on the sides of the drive shaft, engine frame with a length of 150 (cm) and a height of 80 (cm), a funnel top inlet length 30 (cm), back height 6 (cm), long funnel 80 (cm) front height 3 (cm), drum handle 700 (mm), opening handle width 300(mm), opening clamp length 600 (mm).